Outdoor Catering Operations & Innovations: Exploring the Impact of Technological Innovations on Outdoor Catering Operations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Changes in the perspective of the operations and to fulfill the demand of the customer, every industry has seen a dramatic transformation with the use of technology, similarly outdoor catering is also one of the customer service industries which is not left by its embarked presence. Use of various technological systems like online booking system, social media, customer relationship management, tabs and smart phones are enabling the outdoor catering industry to craft a new level segment in customer service. Outdoor catering operation is one of the sectors of hospitality industry where use of smart appliances has made a great influence. As a symbol of showcase i.e. light, camera and action each and everything is on the tips of caterer and customer who ever the end user. Using the technology directly as a part of operations or as assisting appliances in SOP’s the purposefulness and efficiency of implementing these may also depends on the acceptance and skills of staff deployed with the assignment. Even though the technology is been introduced in the operations, but the customer’s service and satisfaction is still of core importance for the caterer and cannot replace the traditional service techniques. The conceptual framework for studying the relationship of innovations and outdoor catering operations is defined on the ground of “trends, issues and challenges”. Top quality food, service, support staff and overall experience is fundamental pillar of the outdoor catering operations, which can be made easier, effective, efficient and memorable to guest with the use of technological innovations.